Comparison of Quality of Life of Elderly Male and Female in Tansen Municipality, Palpa - Sapkota, Laxmi Prasad (Journal of Economics and Management, 2023)
Ensuring a high quality of life (QOL) for elderly individuals is crucial as it directly influences their health, happiness, and overall life satisfaction. The concept of QOL encompasses various factors, including cultural, social, and environmental considerations. Objective: This study aimed to compare the quality of life between elderly males and females residing in Tansen municipality, located in Palpa, western Nepal. A population-based, cross-sectional study design was employed in Tansen municipality, Nepal. The study sample consisted of 102 individuals aged 60 years and above, who were selected using systematic random sampling from wards with a high elderly population (wards 3, 5, and 9). Of the selected participants, 47 were male and 55 were female. Face-to-face interviews were conducted using a standardized, pretested questionnaire as develop by the World Health Organization (WHO) in 1996, known as the WHO BREF questionnaire. Data collection took place from February 10 to March 10, 2018. The collected data were entered and analyzed using IBM SPSS Statistics 20 software. QOL was compared using F and t statistics. Among the participants, 42.6% of males and 52.7% of females had a low QOL, while 57.4% of males and 47.3% of females reported a high QOL. The t statistic (0.034) indicated a significant association between sex and QOL at a significance level of α = 5%. The study also revealed associations between sex, disease, family support, and quality of life, while no significant associations were found with other variables. The study findings suggest that elderly males had a better quality of life compared to females. Additionally, individuals with strong family support exhibited a higher QOL, and disease condition was found to impact QOL.